TELAAH LITERATUR ASPEK-ASPEK PENYEBAB PENGEMBALIAN BERKAS KLAIM BPJS PASIEN RAWAT INAP - Irda Sari; Safira Nur Sabrina; Leni Herfiyanti (POLITEKNIK PIKSI GANESHA, 2020)
This study aims to find out the aspects causing BPJS claim file return of in-patients care.Method used is a literature review that using secondary data, which is collected from 5 earlier journals from different hospitals to obtain main data. From the 5 journals, they are found the aspects causing BPJS claim file return of in-patients care, are completeness and suitability aspects. The factors that cause the incompleteness and mismatch are: (1) Inaccuracy of employee preparing the claim file; (2) No rechecking while inputing the data done by the employee make a mismatch in the claim file; (3) Lack of employee make input data process done in a rush which cause an error in inputing process; (4) Incompleteness in the patients’ medical resume due to doctors in-charge (DPJP) fill them in a rush because of many patients to be handled. As for some suggestions that provided to resolve these problems, are: (1) Re-checking completeness and compatibility of the claims file to minimize the return of them; (2) Increasing thoroughness of the employee in preparing the claim file; (3) Adding Human Resourses in inputing the data; (4) Using Electronic Medical Record in order to simplify the employee and doctors’ work.